2001
DOI: 10.1023/a:1011942824139
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present study was undertaken to determine the effects of AT1 receptor blockade which occurred in response to losartan, on the extracellular matrix (ECM) degradation process in the Bio 14.6 (n = 12) and Bio 53.58 (n = 12) strains which are referred as models of hypertrophic and dilated cardiomyopathy, respectively. The administration of losartan (30 mg/kg/day) in hamsters from 10-20 weeks of age reduced the accumulation of the left ventricular collagen matrix in both of the Bio 14.6 and the Bio 53.58 strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Four trials that met our inclusion criteria were excluded after review of the full manuscript ( supplemental material ) because they were animal research [ 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four trials that met our inclusion criteria were excluded after review of the full manuscript ( supplemental material ) because they were animal research [ 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with the genetic predisposition to develop non-hypertrophic cardiomyopathy (NHCM) but no structural changes or symptoms, it has been suggested that the use of RAAS blockade may be more beneficial than when it is used in patients with left ventricular fibrosis and hypertrophy who have the genetic predisposition to HCM, which supports the hypothesis that ARBs can inhibit gene expression and reduce left ventricular mass in NHCMs [ 9 , 13 , 18 ]. In addition to their effects, different studies have shown that using ARBs and ACE inhibitors is safe [ 14 , 16 , 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Briefly, all ECM components are deposited in larger amounts leading to extensive myocardial fibrosis (Weber 1989). Studies using volume or pressure overload models of heart failure suggest that gene expression of ECM components is largely reversed following treatment with beta-blockers, ACE inhibitors or Angiotensin II receptor blockers (Champetier et al 2009; Grimm et al 2001; Grimm et al 1998; Masutomo et al 2001). The orientation of ECM proteins also changes following an insult.…”
Section: Ecm Changes In Heart Diseasementioning
confidence: 99%